(Ca, K)(Zn, Mn)2As2: Ferromagnetic semiconductor induced by decoupled charge and spin doping in CaZn2As2. (1st July 2022) - Dong, Jinou; Zhao, Xueqin; Fu, Licheng; Gu, Yilun; Zhang, Rufei; Yang, Qiaolin; Xie, Lingfeng; Ning, Fanlong
Abstract: We have successfully synthesized a novel diluted magnetic semiconductor (Ca1−2 x K2 x )(Zn1− x Mn x )2 As2 with decoupled charge and spin doping. The substitutions of (Ca 2+, K + ) and (Zn 2+, Mn 2+ ) in the parent compound CaZn2 As2 (space group P m 1 (No. 164)) introduce carriers and magnetic moments, respectively. Doping only Mn into CaZn2 As2 does not induce any type of long range magnetic ordering. The ferromagnetic ordering arise can only when K + and Mn 2+ are simultaneously doped. The resulted maximum Curie temperature reaches ~7 K, and the corresponding coercive field is ~60 Oe. The transport measurements confirm that samples with K and Mn co-doping still behave like a semiconductor.